1993
DOI: 10.1007/bf02347185
|View full text |Cite
|
Sign up to set email alerts
|

Insects and plants in the pollination ecology of the boreal zone

Abstract: Pollination systems in the boreal zone range from generalist to specialist, both entomologically and botanically. The relative importance of wind pollination, insect pollination, sexual separation between and within plants, and between flowers, hermaphroditism of flowers, and various breeding systems are related to plant growth form and habitat. The diversity and specializations of anthophilous insects parallel those in other bioge0graphic zones, but seem less developed. We suggest that this reflects the combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 119 publications
0
26
0
Order By: Relevance
“…Goodyera repens, Habenaria obtusata and H .orbiculata), Pyrola spp. and Moneses uniflora depend on sexual, rather than clonal, reproduction and on pollinating insects for dispersal of pollen (Kevan et al, 1993). Little is known about the potential impacts of canopy homogenization due to management practices on the ability of understory species to maintain themselves on the landscape.…”
Section: Discussionmentioning
confidence: 98%
“…Goodyera repens, Habenaria obtusata and H .orbiculata), Pyrola spp. and Moneses uniflora depend on sexual, rather than clonal, reproduction and on pollinating insects for dispersal of pollen (Kevan et al, 1993). Little is known about the potential impacts of canopy homogenization due to management practices on the ability of understory species to maintain themselves on the landscape.…”
Section: Discussionmentioning
confidence: 98%
“…In our attempt to dichotomize vectors, the ambiguous position of Plantago is of interest, because there are accounts of ambophily (biotic and wind pollination) in P. lanceolata (Clifford 1962;Stelleman 1984b) and in P. major (Kevan et al 1993). Pollenkitt and, by extension, pollen aggregation in this species may improve the likelihood of biotic pollination, especially since their anemophilous pollination syndrome precludes some typical strategies (i.e., attractants and rewards) used by zoophilous species in biotic pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Although detailed observation of the floral visitors to flowers of M. trifoliata was not done in this study, the impoverished nature of the pollinator fauna on the island of Newfoundland is clear. Insular Newfoundland has only about 40% of the Apoidea (34 of 97 species) and Syrphidae (36 of 86 species) species diversity found in mainland boreal (northern Ontario) sites where M. trifoliata is common (Constantine 1986;Vockeroth 1992;Kevan et al 1993). In addition to the three species of bumblebees, a variety of visitors are commonly found foraging on M. trifoliata flowers, including syrphid and other species of flies, butterflies, and rarely, honey bees.…”
Section: Compatibilitymentioning
confidence: 98%
“…The pollinator fauna of insular Newfoundland is not well documented, but comparisons of species number of the major pollinator groups (Apoidea: Kevan et al 1993, andSyrphidae: Vockeroth 1992) with those found in the continental boreal ecosystem indicate a depauperate fauna (Constantine 1986). Populations of important pollinators such as bumblebees are small, a consequence of the cool, wet weather (D. Larson, personal communication).…”
mentioning
confidence: 99%